Latin America and the Caribbean : Getting Fit for the Next Big Challenge - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses how to boost Latin America’s growth. The region needs to increase productivity, spur innovation, and adapt its productive structure to changing circumstances which must become a national priority for all countries, independent of their political cycles and ideologies. Improving logistics and infrastructure, education, and the contractual environment are critical to advance development in the region. World Bank Group is working with the Haitian Government and the private sector to introduce best practices in public-private partnerships and to create opportunities for the Haitian people who have been waiting so long for them. He concludes by saying that providing disadvantaged children access to a quality education raises their productive capacity and enhances social inclusion through higher employability leading to higher growth and improved quality of life.